2015
DOI: 10.1002/pssa.201431719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a GaN cap layer on the reliability of AlGaN/GaN Schottky diodes

Abstract: In this paper, AlGaN/GaN‐ and GaN/AlGaN/GaN‐based Schottky barrier diodes (SBDs) were fabricated and studied for comparison. The recorded electrical characteristics of the devices show that the introduction of a GaN cap layer can evidently reduce the reverse leakage current and suppress the forward current decay of the devices. What is more important, the GaN/AlGaN/GaN‐based SBDs are capable of greatly alleviating the unrecoverable degradation of the reverse characteristics, which was observed in the device wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…These improved properties are obviously attributed to the low leakage current by using the u-GaN cap. With the u-GaN, a lower ideality factor and a higher Schottky barrier height is enabled, as has been reported that by designing an InGaN, InGaAs, and GaN cap layers to enhance the Schottky barrier height in the literature. It was suggested that an electric field pointing from the surface of the GaN toward the AlGaN layer was formed by the negative polarization charge at the interface.…”
Section: Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These improved properties are obviously attributed to the low leakage current by using the u-GaN cap. With the u-GaN, a lower ideality factor and a higher Schottky barrier height is enabled, as has been reported that by designing an InGaN, InGaAs, and GaN cap layers to enhance the Schottky barrier height in the literature. It was suggested that an electric field pointing from the surface of the GaN toward the AlGaN layer was formed by the negative polarization charge at the interface.…”
Section: Results and Discussionmentioning
confidence: 97%
“…On the other hand, the decreased ideal factor due to the introduction of the GaN cap layer implies the suppression of the tunneling current. 51 These two effects lead to the decrease of the total leakage. Additionally, the extracted field-effect mobility is estimated to be 1153 and 1145 cm 2 /V/s at a V ds of 10 V for MOS-HEMT and MOS-HEMT with u-GaN cap structures, respectively (the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface morphology of the GaN HEMT grown on a) an Fe‐doped buffer layer (50×) as reported in our previous work, [ 18 ] b) an Fe‐doped buffer layer (20×), and c) an unintentionally doped buffer layer after the LLO process.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 ] In the growth process of the Fe‐doped GaN buffer layer, the flow of the Fe source gas was 300 sccm; more details on the growth conditions can be found elsewhere. [ 17,18 ] The GaN HEMTs were debonded from the sapphire substrate using an LLO system comprising a set of optical lenses, working chamber, and KrF excimer laser that supplies UV light at a wavelength of 193 nm and a short pulse duration of 25 ns.…”
Section: Methodsmentioning
confidence: 99%